A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature and a preparation method thereof

By combining magnetic rare earth materials with other materials, magnetic rare earth friction materials with the same direction of friction coefficient and temperature are prepared, which solves the problem of the reduction of friction coefficient of traditional friction materials at high temperatures, and achieves more stable braking performance and higher safety.

CN114151479BActive Publication Date: 2025-03-07GUANGZHOU ANKODA AUTOMOBILE BRAKE SYST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111389914.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-22
Publication Date
2025-03-07
Estimated Expiration
2041-11-22

AI Technical Summary

Technical Problem

When the temperature of the traditional brake pad friction material increases, the friction coefficient is unstable, which can easily lead to brake failure and affect braking performance and safety.

Method used

A combination of magnetic rare earth material with fibers, resins, friction adjustment materials, graphite and fillers is used to prepare magnetic rare earth friction materials with the same direction of friction coefficient and temperature through dry press forming process.

Benefits of technology

The high temperature resistance, wear resistance and creep resistance of friction materials are improved, the friction coefficient increases with the increase of temperature, avoid the risk of brake failure, and improve the effectiveness and safety of the brake system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003368335800000061
    Figure BDA0003368335800000061
Patent Text Reader

Abstract

The present invention discloses a magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature, comprising the following components: 15-30% paramagnetic rare earth material, 15-25% fiber, 4-8% resin, 10-20% friction adjustment material, 8-15% graphite, and 20-30% filler; its preparation steps are: mixing, hot pressing, heat treatment, and size processing. The present invention adopts a paramagnetic rare earth material, and a combination of a fiber material, a high temperature resistant resin, a friction adjustment material, a lubricating material, and a filling material for pressing and forming; according to the principle that the magnetic susceptibility of the paramagnetic rare earth material is inversely proportional to the temperature, when the temperature of the paramagnetic rare earth material rises, the magnetic susceptibility decreases, the lubricity decreases, and the friction coefficient of the material increases, thereby achieving the change of the friction coefficient in the same direction as temperature; the overall performance of the friction material is adjusted by resin, friction adjustment material, graphite, and filler, so that it has good friction performance, mechanical performance, and physical performance, thereby ensuring the effectiveness, safety, and stability of the braking function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of friction materials, and in particular to a magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature and a preparation method thereof. Background Art

[0002] Brake pads are an important component of the vehicle braking system, the most critical safety component, and play a decisive role in the braking effect. The performance of brake pad friction materials is an important factor affecting the braking performance of brakes. Friction materials are mainly used in power machinery. Due to the uneven microscopic surface structure of the material, it will have a certain hindering effect on the dual material in contact with it and in a state of relative motion. This effect can drive the friction material and the dual material to finally be in a relatively static state, and at the same time absorb and conduct the kinetic energy of this process and convert it into heat energy of the friction material.

[0003] With the increase of braking pressure and initial braking speed, and the frequency of braking, the temperature of the friction material gradually increases, resulting in: (1) heat penetrates into the material matrix, softening or even burning the resin and other binders, reducing the bonding strength between the reinforcing fiber and the matrix, and causing the fiber to be pulled out of the matrix and peel off; (2) under the action of thermal stress, the surface friction material will deform, crack, and fall off, forming fine wear debris, which will weaken the bonding strength with the matrix, increase wear, reduce friction stability, and easily produce violent vibration and noise; (3) when the friction surface temperature exceeds the thermal decomposition temperature, the friction material will undergo thermal decay. The so-called "thermal decomposition temperature" refers to the critical temperature at which the friction coefficient drops sharply when the temperature of the heat-affected surface layer rises to a certain value. The thermal decomposition of the matrix and the friction layer will release gas, produce "cavitation" phenomenon, and fatigue cracks. The cracks in the matrix and the friction layer grow and expand under the action of braking pressure, forming granular or flaky wear debris, reducing the braking torque and affecting the braking performance of the brake.

[0004] Therefore, under normal circumstances, as the temperature of the brake pad increases, the friction coefficient increases unstably at first, and when it reaches a certain temperature, the friction coefficient suddenly decreases, which can easily cause "brake failure" and lead to accidents. The friction material used in traditional brake pads can still stabilize the friction coefficient at medium and normal temperatures. Once the brake temperature rises to about 300℃, its friction coefficient will decrease, causing the braking force to decrease, which is very likely to cause traffic accidents. Therefore, developing a friction material that can increase the friction coefficient as the working temperature of the brake pad increases is the best solution to this problem.

[0005] Chinese invention patent CN201310182211.7 discloses an automobile brake pad using ionic rare earth slag as filler, including 10-15% ionic rare earth slag, 20-30% mineral fiber, 10-15% binder, 15-25% graphite, 2-5% high temperature binder, 1-3% aramid reinforced fiber, and 5-10% friction-increasing material. The invention uses rare earth slag to replace traditional mineral fillers, which improves the friction coefficient stability and high temperature performance of the brake pad to a certain extent, but the friction coefficient will still decrease to a certain extent with the increase of temperature. Summary of the invention

[0006] In view of the above problems, the primary purpose of the present invention is to provide a magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature and a preparation method thereof. Based on the principle that the magnetic susceptibility of paramagnetic rare earth materials is inversely proportional to the temperature, a magnetic rare earth friction material whose friction coefficient increases with increasing temperature is developed, thereby overcoming the shortcomings of the prior art that the friction coefficient of brake pads is unstable and the friction coefficient decreases with increasing temperature, thereby improving the effectiveness and safety of the braking system.

[0007] A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature comprises the following components: 15% to 30% paramagnetic rare earth material, 15% to 25% fiber, 4% to 8% resin, 10% to 20% friction adjustment material, 8% to 15% graphite and 20% to 30% filler.

[0008] Preferably, the paramagnetic rare earth material comprises one or more of gadolinium oxide, samarium oxide, dysprosium oxide, holmium oxide, erbium oxide, cerium oxide, cerium fluoride, europium oxide, and europium fluoride; preferably, 33% gadolinium oxide + 33% europium fluoride + 34% erbium oxide; terbium oxide, terbium fluoride, lanthanum oxide, metallic lanthanum powder, ytterbium oxide, ytterbium powder, neodymium oxide, neodymium fluoride and other rare earth materials can also be used.

[0009] Preferably, the paramagnetic rare earth material is a nano-scale paramagnetic rare earth material that has been magnetized, and the paramagnetic strength of the nano-scale paramagnetic rare earth is increased to 10 -4 ~10 -1 emu / g.

[0010] Preferably, the fiber material comprises one or more of quartz fiber, aramid fiber, acrylonitrile fiber, ceramic fiber, copper fiber, viscose fiber, and glass fiber; preferably 25% quartz fiber + 30% aramid fiber + 20% glass fiber + 15% copper fiber + 10% viscose fiber, and fiber materials such as mineral fiber, carbon fiber, basalt fiber, and hemp fiber can also be used.

[0011] Preferably, the resin comprises one or more of phenolic resin, modified epoxy resin, modified acrylic resin, and modified phenolic resin; phenolic resin is preferred, and silicone rubber and silicone resin may also be used.

[0012] Preferably, the friction adjustment material comprises one or more of molybdenum disulfide, antimony sulfide, talcum powder, mica powder, rubber powder, and cashew nut shell powder; preferably 35% talcum powder + 15% molybdenum disulfide + 25% mica powder + 25% cashew nut shell powder.

[0013] Preferably, the graphite comprises one or more of flake graphite, expanded graphite, graphene, and crystalline graphite; preferably 30% expanded graphite + 35% flake graphite + 35% graphene.

[0014] Preferably, the filler comprises one or more of potassium feldspar, barite, calcite, alumina, copper oxide, brown corundum, diatomaceous earth, cryolite, quartz powder, bauxite, and vermiculite, preferably 18% potassium feldspar + 33% quartz powder + 17% bauxite + 32% barite.

[0015] A method for preparing a magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature, using a dry pressing process, is carried out in the following four steps:

[0016] (1) Mixing: Weigh the paramagnetic rare earth material, fiber, resin, friction adjustment material, graphite, and filler in proportion, put all the materials into a high-speed mixer in order, and stir for 8 to 10 minutes to complete the mixing of the materials;

[0017] (2) Hot pressing: The mixed materials are evenly placed in the mold, and the mold temperature is controlled at 150±5°C, the pressing pressure is 30±2MPa, and the heat preservation and pressure holding time is 20-30s / mm. The hot pressing is performed under the conditions of venting for 15S at the beginning of the hot pressing, and then venting for 5S each time at an interval of 10S, and venting is performed 3 to 5 times;

[0018] (3) Heat treatment: heat treatment of the hot pressed material;

[0019] (4) Dimension processing: The heat-treated material is processed by special grinding equipment to control the flatness of the friction plate within 0.2 mm.

[0020] Preferably, the specific process of heat treatment in step (3) is: from room temperature to 80°C, heat at a constant rate for 40 minutes, and keep warm for 20 minutes; from 80°C to 130°C, heat at a constant rate for 40 minutes, and keep warm for 20 minutes; from 130°C to 160°C, heat at a constant rate for 40 minutes, and keep warm for 20 minutes; from 160°C to 190°C, heat at a constant rate for 40 minutes, and keep warm at 190°C for 150 minutes, and finally cool to room temperature at a rate of 20°C / hour.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention adopts paramagnetic rare earth material, and compresses and forms a combination of fiber material, high temperature resistant resin, friction adjustment material, lubricating material and filling material, which has good friction performance, mechanical performance, physical performance and noise reduction, effectively improves the high temperature resistance, wear resistance and creep resistance of the friction material, and makes the friction coefficient increase with the increase of temperature, which can effectively prevent the accidental situation of brake failure caused by the decrease of friction coefficient due to excessively high brake temperature.

[0023] 2. Use rare earth materials that have been magnetized and have strong magnetic properties. According to relevant research, the stronger the paramagnetism of the magnetic rare earth, the higher the friction and lubrication performance it can exhibit at room temperature; and the paramagnetism of the magnetic rare earth material decreases with increasing temperature.

[0024] The present invention adopts a nano-paramagnetic rare earth material that has been magnetized. At room temperature, the rare earth material has a high paramagnetic strength and exhibits a high lubrication performance. At this time, the lubricity of the rare earth material effectively reduces the high friction of the fiber friction material, so that the friction coefficient of the brake pad is controlled within a reasonable range, avoiding the situation where the wheel suddenly locks due to too high a friction coefficient.

[0025] As the braking operation causes the temperature of the brake pad to gradually rise, the paramagnetic strength of the rare earth material gradually decreases, causing the lubrication performance of the rare earth material to decrease accordingly. At this time, the lubrication performance of the rare earth material gradually declines, and the relatively stable high friction of the fiber friction material gradually becomes prominent, showing that the friction coefficient increases with increasing temperature, thereby improving the effectiveness and safety of the braking system.

[0026] 3. The addition of rare earth materials makes the interface between resin and fiber play the role of intermediate medium, thereby improving the interface bonding performance, improving the fusion state between the components, and playing the role of refining, deep purification and refinement, thereby improving the friction performance, mechanical properties and physical properties of the material.

[0027] 4. Use fiber friction materials with high temperature resistance and high friction coefficient stability, such as quartz fiber, aramid fiber, glass fiber, etc. In particular, high-quality quartz fiber has a high temperature tolerance of over 1500°C and can also maintain a high friction coefficient stability.

[0028] 5. Using high temperature resistant resin materials as binders and reasonably controlling their ratio can effectively improve the thermal decay performance, recovery performance, wear performance and mechanical properties of brake pads, and can significantly improve the high temperature resistance of brake pads;

[0029] 6. On the basis of stable fiber friction materials, paramagnetic rare earth materials are used to achieve the same change of friction coefficient and temperature. The overall performance of the friction material is adjusted through resin, friction adjustment material, graphite and filler to make it have good friction performance, mechanical performance and physical properties, thereby ensuring the effectiveness, safety and stability of the braking function, and preventing thermal decay.

[0030] 7. The invention has simple process, strong controllability, low cost, strong practicability and good application prospect. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] Embodiment 1:

[0033] A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature comprises the following components: 20% paramagnetic rare earth material, 20% fiber, 5% resin, 10% friction adjustment material, 15% graphite and 30% filler.

[0034] The paramagnetic rare earth material is 33% gadolinium oxide + 33% europium fluoride + 34% erbium oxide; all of them are magnetized nano-paramagnetic rare earth materials, and the paramagnetic strength of the nano-paramagnetic rare earth is increased to 10 by a powder magnetizer. -4 ~10 -1 emu / g;

[0035] The fiber material is quartz fiber 25% + aramid fiber 30% + glass fiber 20% + copper fiber 15% + viscose fiber 10%;

[0036] The resin material is phenolic resin;

[0037] The friction adjustment material is 35% talc powder + 15% molybdenum disulfide + 25% mica powder + 25% cashew nut shell powder;

[0038] The graphite is 30% expanded graphite + 35% flake graphite + 35% graphene;

[0039] The filler is 18% potassium feldspar + 33% quartz powder + 17% bauxite + 32% barite.

[0040] A method for preparing a magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature, using a dry pressing process, is carried out in the following four steps:

[0041] (1) Mixing: Weigh the paramagnetic rare earth material, fiber, resin, friction adjustment material, graphite, and filler in proportion, put all the materials into a high-speed mixer in order, and stir for 8 to 10 minutes to complete the mixing of the materials;

[0042] (2) Hot pressing: The mixed materials are evenly placed in the mold. The mold temperature is controlled at 150±5°C, the pressing pressure is 30±2MPa, and the heat preservation and pressure holding time is 25s / mm. The hot pressing is performed under the conditions of venting for 15S at the beginning of the hot pressing, and then venting for 5S each time at an interval of 10S, and venting is performed 3 to 5 times;

[0043] (3) Heat treatment: from room temperature to 80°C, increase the temperature at a constant rate for 40 minutes, and keep it at a constant rate for 20 minutes; from 80°C to 130°C, increase the temperature at a constant rate for 40 minutes, and keep it at a constant rate for 20 minutes; from 130°C to 160°C, increase the temperature at a constant rate for 40 minutes, and keep it at a constant rate for 20 minutes; from 160°C to 190°C, increase the temperature at a constant rate for 40 minutes, and keep it at 190°C for 150 minutes, and finally cool it to room temperature at a rate of 20°C / hour;

[0044] (4) Dimension processing: The heat-treated material is processed by special grinding equipment to control the flatness of the friction plate within 0.2 mm.

[0045] Embodiment 2:

[0046] The difference between this embodiment 2 and embodiment 1 is that:

[0047] A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature comprises the following components: 23% paramagnetic rare earth material, 18% fiber, 8% resin, 16% friction adjustment material, 12% graphite and 23% filler.

[0048] Experimental data:

[0049] According to the formula and preparation process of Example 1 and Example 2, samples of Formula 1 and Formula 2 were tested for temperature and friction coefficient changes according to the implementation standard of GB5763-2008 Brake Linings for Automobiles. The test results are shown in the following table.

[0050]

[0051] From the friction performance test results, it can be seen that as the temperature increases, both Formula 1 and Formula 2 can stably increase the friction coefficient, thereby ensuring the effectiveness and safety of the braking function. Even in the cooling stage, the friction coefficient of the friction material of the present invention can be slightly higher than that in the heating stage, and thermal decay will not occur, which can ensure the stability of the braking performance.

[0052] Embodiment 3:

[0053] The difference between this embodiment 3 and embodiment 1 is that:

[0054] A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature comprises the following components: 15% paramagnetic rare earth material, 15% fiber, 8% resin, 20% friction adjustment material, 14% graphite and 28% filler.

[0055] Specifically, the paramagnetic rare earth material is a combination of samarium oxide, erbium oxide, cerium oxide, and europium fluoride; all of them are magnetized nano-scale paramagnetic rare earth materials, and the paramagnetic strength of the nano-scale paramagnetic rare earth is increased to 1 by a powder magnetizer. 0-4 ~1 0-1 emu / g

[0056] The fiber material is a combination of quartz fiber, aramid fiber, acrylonitrile fiber, ceramic fiber, copper fiber, viscose fiber and glass fiber.

[0057] The resin is a combination of phenolic resin, modified epoxy resin, modified acrylic resin and modified phenolic resin;

[0058] The friction adjustment material is a combination of antimony sulfide, talcum powder, mica powder, and rubber powder;

[0059] The graphite is a combination of graphene and crystalline graphite;

[0060] The filler is a combination of calcite, alumina, copper oxide and vermiculite.

[0061] Embodiment 4:

[0062] The difference between this embodiment 4 and embodiment 1 is that:

[0063] A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature comprises the following components: 30% paramagnetic rare earth material, 25% fiber, 7% resin, 10% friction adjustment material, 8% graphite and 20% filler.

[0064] Specifically, the paramagnetic rare earth material is a combination of gadolinium oxide, dysprosium oxide, and holmium oxide, all of which are magnetized nano-paramagnetic rare earth materials, and the paramagnetic strength of the nano-paramagnetic rare earth is increased to 1 by a powder magnetizer. 0-4 ~1 0-1 emu / g;

[0065] The fiber material is a combination of quartz fiber, aramid fiber, acrylonitrile fiber and ceramic fiber;

[0066] The resin is a combination of modified epoxy resin and modified phenolic resin;

[0067] The friction adjustment material is a combination of molybdenum disulfide, antimony sulfide, talcum powder and mica powder;

[0068] The graphene is a combination of expanded graphite and graphene;

[0069] The filler is a combination of brown corundum, diatomaceous earth, cryolite and bauxite.

[0070] Embodiment 5:

[0071] The difference between this embodiment 5 and embodiment 1 is that:

[0072] A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature comprises the following components: 25% paramagnetic rare earth material, 20% fiber, 4% resin, 15% friction adjustment material, 11% graphite and 25% filler.

[0073] The paramagnetic rare earth material is a combination of gadolinium oxide, samarium oxide and europium fluoride; all of them are magnetized nano-paramagnetic rare earth materials, and the paramagnetic strength of the nano-paramagnetic rare earth is increased to 1 by a powder magnetizer. 0-4 ~1 0-1 emu / g;

[0074] The fiber material is a combination of ceramic fiber, copper fiber, viscose fiber and glass fiber;

[0075] The resin is a combination of phenolic resin and modified phenolic resin;

[0076] The friction adjustment material is a combination of molybdenum disulfide, antimony sulfide, talcum powder and mica powder;

[0077] The graphite is graphene;

[0078] The filler is a combination of barite, calcite, alumina and copper oxide.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, combination, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature, characterized in that: The magnetic rare earth friction material comprises the following components by weight percentage: 15% to 30% paramagnetic rare earth material, 15% to 25% fiber, 4% to 8% resin, 10% to 20% friction adjustment material, 8% to 15% graphite, and 20% to 30% filler; The paramagnetic rare earth material is a combination of gadolinium oxide, europium fluoride and erbium oxide, or a combination of samarium oxide, erbium oxide, cerium oxide and europium fluoride, or a combination of gadolinium oxide, samarium oxide and europium fluoride; The paramagnetic rare earth material is a nano-scale paramagnetic rare earth material that has been magnetized. The paramagnetic strength of the nano-scale paramagnetic rare earth is increased to 1 by a powder magnetizer. 0-4 ~1 0-1 emu / g.

2. The magnetic rare earth friction material according to claim 1, wherein the friction coefficient changes in the same direction as the temperature, characterized in that: The fiber material includes one or more of quartz fiber, aramid fiber, acrylonitrile fiber, ceramic fiber, copper fiber, viscose fiber and glass fiber.

3. The magnetic rare earth friction material according to claim 1, wherein the friction coefficient changes in the same direction as the temperature, The resin comprises one or more of phenolic resin, modified epoxy resin, modified acrylic resin and modified phenolic resin.

4. The magnetic rare earth friction material according to claim 1, wherein the friction coefficient changes in the same direction as the temperature, The friction adjustment material comprises one or more of molybdenum disulfide, antimony sulfide, talcum powder, mica powder, rubber powder, and cashew nut shell powder.

5. The magnetic rare earth friction material according to claim 1, wherein the friction coefficient changes in the same direction as the temperature, characterized in that: The graphite includes one or more of flake graphite, expanded graphite, graphene, and crystalline graphite.

6. The magnetic rare earth friction material according to claim 1, wherein the friction coefficient changes in the same direction as the temperature, characterized in that: The filler comprises one or more of potassium feldspar, barite, calcite, aluminum oxide, copper oxide, brown corundum, diatomaceous earth, cryolite, quartz powder, bauxite and vermiculite.

7. The method for preparing a magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature as claimed in any one of claims 1 to 6, characterized in that: The steps include: (1) Mixing: Weigh the paramagnetic rare earth material, fiber, resin, friction adjustment material, graphite, and filler in proportion, put all the materials into a high-speed mixer in order, and stir for 8 to 10 minutes to complete the mixing of the materials; (2) Hot pressing: The mixed materials are evenly placed in the mold, and the mold temperature is controlled at 150±5°C, the pressing pressure is 30±2MPa, and the heat preservation and pressure holding time is 20-30s / mm. The hot pressing is performed under the conditions of venting for 15S at the beginning of the hot pressing, and then venting for 5S each time at an interval of 10S, and venting is performed 3 to 5 times; (3) Heat treatment: heat treatment of the hot pressed material; (4) Dimension processing: The heat-treated material is processed by special grinding equipment to control the flatness of the friction plate within 0.2 mm.

8. The method for preparing a magnetic rare earth friction material whose friction coefficient changes in the same direction as temperature according to claim 7, characterized in that: The specific process of heat treatment in step (3) is as follows: from room temperature to 80°C, heating at a constant rate for 40 minutes, and keeping warm for 20 minutes; from 80°C to 130°C, heating at a constant rate for 40 minutes, and keeping warm for 20 minutes; from 130°C to 160°C, heating at a constant rate for 40 minutes, and keeping warm for 20 minutes; from 160°C to 190°C, heating at a constant rate for 40 minutes, and keeping warm at 190°C for 150 minutes, and finally cooling to room temperature at a rate of 20°C / hour.

Citation Information

Patent Citations

  • A type of automotive brake pad using ion-type rare earth slag as filler

    CN103267075B

  • Rare-earth oxide modified resin-based automotive brake friction material and preparation method thereof

    CN106051006A